Sewage input reduces the consumption of Rhizophora mangle propagules by crabs in a subtropical mangrove system. (December 2016) - Boehm, Frederike Ricarda; Sandrini-Neto, Leonardo; Moens, Tom; da Cunha Lana, Paulo
Abstract: Mangrove forests are highly productive and play a major role in global carbon cycling. Their carbon accumulation can be influenced through the consumption of nutrient-poor leaves and propagules by herbivore crabs. Anthropogenic nutrient input from sewage contamination is widespread in these often naturally nutrient-limited ecosystems. We hypothesised that sewage-mediated nutrient input to mangrove stands of Paranaguá Bay (southern Brazil), would alter the nutrient sources available for crabs, e.g. through microphytobenthos increase, and that this would reflect in their feeding behaviour. We predicted that propagules of Rhizophora mangle in contaminated stands would experience lower grazing pressure from their two main local consumers (Ucides cordatus and Goniopsis cruentata) . We compared herbivory rates on R. mangle propagules in sewage contaminated and uncontaminated mangrove stands. We found that herbivory rates were significantly lower in contaminated than uncontaminated forests, but this pattern could not be clearly attributed to increased nutrient availability. Highlights: Propagule herbivory rates were measured in sewage contaminated and unaffected sites. Ucides cordatus was the main consumer of Rhizophora mangle propagules in the area. Propagule herbivory rates were significantly lower in sewage contaminated mangroves.